Artificial Intelligence Based Halal Compliance Model Civil Law Perspective - Rafianti, Fitri; Erika, Winda; Damanik, Rusli Efendi; Harahap, Aswindari (Judge : Jurnal Hukum, 2025)
The purpose of this study is to examine and analyze the role of the "Artificial Intelligence-Based Halal Compliance Model (AI) from a Civil Law Perspective." Specifically, this study identifies how AI can help ensure product compliance with halal standards in the context of Indonesian civil law. In addition, it also examines the role of contracts and agreements between producers, certification bodies, and consumers in influencing the effectiveness of the halal compliance system. Civil law is used to analyze legal implications, particularly regarding liability, contract validity (smart contract validity), and evidence arising from the application of the Halal Compliance Model based on AI, which plays an important role in ensuring the integrity and traceability of halal products throughout the supply chain. In civil contract law, AI is used to automate, analyze, and even execute contracts through the concept of Smart Contracts. The interconnection between civil law and AI raises new challenges and opportunities, especially in the issues of liability and legal personality.